1997
DOI: 10.1128/jvi.71.11.8918-8922.1997
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 2 envelope glycoprotein binds to CD8 as well as to CD4 molecules on human T cells

Abstract: We report here that human immunodeficiency virus type 2 (HIV-2) envelope glycoprotein (gp105), but not HIV-1 gp120, can bind to CD8 molecules as well as to CD4 molecules on human T cells. This phenomenon may lead to differences in the life cycles of HIV-1 and HIV-2, and it may be related to the differences in disease manifestations of HIV-1 and HIV-2 infection, including longer survival of HIV-2-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…We recently reported that HIV‐2/gp105 (but not HIV‐1/gp120) bound to CD8 + T cells as well as CD4 + T cells purified from PBMC in a HIV‐2/gp105 concentration‐dependent fashion. 10 This HIV‐2/gp105 binding was observed in a CD4 − CD8 + human T‐cell line (a variant of MOLT‐4 cells) and a human CD8‐transfected mouse T‐cell hybridoma, in addition to human CD8 + T cells. We also reported that the binding site of HIV‐2/gp105 was located on the α‐chain of CD8 and not the β‐chain, and that it overlapped with the site for a Leu 2a antibody.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently reported that HIV‐2/gp105 (but not HIV‐1/gp120) bound to CD8 + T cells as well as CD4 + T cells purified from PBMC in a HIV‐2/gp105 concentration‐dependent fashion. 10 This HIV‐2/gp105 binding was observed in a CD4 − CD8 + human T‐cell line (a variant of MOLT‐4 cells) and a human CD8‐transfected mouse T‐cell hybridoma, in addition to human CD8 + T cells. We also reported that the binding site of HIV‐2/gp105 was located on the α‐chain of CD8 and not the β‐chain, and that it overlapped with the site for a Leu 2a antibody.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that the binding site of HIV‐2/gp105 was located on the α‐chain of CD8 and not the β‐chain, and that it overlapped with the site for a Leu 2a antibody. 10 The decrease of Leu 2a antibody binding to CD8 + T cells treated with HIV‐2/gp105 was thought to be due to competition for binding between HIV‐2/gp105 and the antibody ( Fig. 1f).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more "open" structure of gp105 is thought to explain the broader range of co-receptor usage by HIV-2 than HIV-1 isolates [21] and the higher levels of neutralizing antibodies documented in HIV-2infected patients [22]. Moreover, gp105 ROD was shown to bind to the CD8 molecule with high affinity, whereas HIV-1 IIIB gp120 was unable to [23]. We show here that HIV-2 Env markedly suppresses TCR-mediated responses through a mechanism dependent upon the contact between monocytes and T cells.…”
Section: Introductionmentioning
confidence: 99%